KUALITAS PELAYANAN ADMINISTRASI KEPENDUDUKAN PADA MAL PELAYANAN PUBLIK KABUPATEN PONOROGO PROPINSI JAWA TIMUR TAHUN 2022 - Hartono, Cuk; Haryanto, Aris Tri; Purwanto, Adi (JI@P, 2023)
This research aims to describe the quality of population administration services at the Ponorogo Regency Public Service Mall. In this study, the research methodology used by the author is a descriptive research method with a qualitative approach with a view to focusing attention on the problems or phenomena that existed at the time the research was conducted. The key informants of the research were the Head of the Department of Population and Civil Registration. To measure service quality, it is necessary to have five indicators or better known as ’dimensions’, which include: Tangibles, reliability, responsiveness, Assurance, , Empathy. Based on the results of data presentation and analysis, it can be concluded that in general the quality of population administration services at the Ponorogogo Regency Public Service Mall is good, needs to be improved such as discipline in service hours and friendliness of officers at the service counter. Keywords: Tangibles, reliability, responsiveness, assurance, empathy